The perfection of desire: habit, reason, and virtue in Aquinas's "Summa theologiae" - Porter, Jean (The Pere Marquette theology lecture, 2018)
Habits as principles of action -- Virtue, perfection, and reason -- Habits and virtues of the will -- Concluding remarks on infused and acquired virtues